Enquadramento de corpos de água em bacias hidrográficas. Estudo de caso: Microbacia do Arroio Jararaca - (:unkn) unknown (Universidade Federal do Pampa, 2017)
The present work aims to characterize a water quality of Arroio Jararaca watershed, classifying it in a comparative way with the current scenario provided by the legislation. The data are obtained from sample collections at three points of Arroio Jararaca, analyzed in the laboratory and finally compared and classified according to the adjustment required by legislation for the definition of the class of framing. The present study is justified by the need to evaluate the current scenario of the water quality of the contributing watersheds of the Ibirapuitã River, seeking to identify a participation of this Stream in the process of degradation of water quality. The locations of sampling points and sampling points were defined, instead of material sent by a laboratory for a test of analysis of some indicators, comparing the scenario found with other results, for example, Water points in these.
Keywords: Engenharia civil; Hidrologia; Águas doces; Microbacia; Hydrology; Arroio Jararaca.; Civil engineering; Sweet water; CNPQ::ENGENHARIAS